The Rhetoric of Paintings: Balinese Painters, Dutch Colonists and the Question of Gender Relationships in 19th and Early 20th Century Bali - Peter Worsley (Jurnal Kajian Bali (Journal of Bali Studies), 2021)
The present essay is about the interpretation of paintings and how an interest which Balinese painters display in gender relationships in the context of illustrations of ritual in their narrative works on the one hand, contrasts with strong expressions of Dutch disapproval of the despotic nature of the rule of Balinese kings and consequentially the unjust treatment of women in Balinese society on the other. With this in mind, the present paper first considers the representation of gender relationships in a number of Balinese paintings from the nineteenth and early twentieth centuries and then turns to a discussion of the understanding of Balinese gender relationships of two members of Dutch colonial society in the Dutch East Indies, one a senior bureaucrat, Graaf C.W.S van Hogendorp and the other the protestant missionary R. van Eck. I discuss a play by Graaf C.W.S van Hogendorp, ‘Pièce de Circonstance sur la conquête de Bali 1846’, written to celebrate the victory of the Dutch army over the Kingdom of Buleleng in 1846 and an article about ‘Het Lot der Vrouw op Bali’ (‘The lot of the Balinese woman’), published in the journal Tijdschrift voor Indische Taal-, Land-, en Volkenkunde in 1872 by the protestant missionary R. van Eck.